The Description of Animal Protein Consumption Bahavior in Stunted Children at Sidorejo Village in Pulokulon - Bintang Restu Dewangga; Ratih Dwilestari Puji Utami; Atiek Murharyati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition so that their height is too short for their age (Nadila, 2023). Approximately 30.8% of toddlers in Indonesia are stunting. Children aged >12 months are more likely to experience stunting than children of the same age. This is due to the older the child, the greater the need for nutrients required to burn energy in the body. Based on the SSGI results in 2021, the national stunting rate decreased by 1.6% per year from 27.7% in 2019 to 24.4%; in 2021, almost all of the 34 provinces showed a decrease compared to the year (Hatijar, 2023). Toddlers need more protein for muscle and antibody formation. Protein needs for the 1-3 year old group are 20 grams, 4-6 year olds are 25 grams, and 7-9 year olds are 40 grams. Animal protein sources can be found in fish, eggs, chicken, milk, and meat, which have complete and high-quality essential amino acid content. Essential amino acids in animal protein are obtained from the food we consume. The benefits of essential amino acids are as wound healers, growth hormone production, increases muscle strength, and regulates blood sugar levels. The results of the analysis of the description of animal protein consumption behavior according to the age group of stunted toddlers at Sidorejo Village in Pulokulon found that 95% of stunted toddlers consume less animal protein.